2013
DOI: 10.1038/aps.2013.154
|View full text |Cite
|
Sign up to set email alerts
|

(−)Doxazosin is a necessary component for the hypotensive effect of (±)doxazosin during long-term administration in conscious rats

Abstract: Aim: Doxazosin is a racemic mixture of (-)doxazosin and (+)doxazosin that is currently used as an add-on therapy for hypertension. In this study we investigated the contribution of each enantiomer to the hypotensive action of long-term administration of (±)doxazosin in conscious rats. Methods: Blood pressure of conscious SD rats was measured using a volume pressure recording system. The rats were orally administered (-)doxazosin, (+)doxazosin, or (±)doxazosin (8 mg·kg -1 ·d -1 ) for 12 weeks. Plasma concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…NA is a neurotransmitter released from sympathetic nerve endings that activate α 1 -adrenoceptors on the cell membrane of vascular smooth muscle to produce vasoconstriction, and activates β 2 -adrenoceptors to produce vasodilation. In in vitro experiments, both the neuronal uptake and the nonneuronal uptake of NA also significantly affected NA-induced vasoconstriction [16,[24][25][26] . Whether LE affected the neuronal uptake and nonneuronal uptake of NA is unknown, and the activation of α 2 -adrenoceptors and β 2 -adrenoceptors by NA was not ruled out in the study by Lee et al [23] .…”
Section: Discussionmentioning
confidence: 99%
“…NA is a neurotransmitter released from sympathetic nerve endings that activate α 1 -adrenoceptors on the cell membrane of vascular smooth muscle to produce vasoconstriction, and activates β 2 -adrenoceptors to produce vasodilation. In in vitro experiments, both the neuronal uptake and the nonneuronal uptake of NA also significantly affected NA-induced vasoconstriction [16,[24][25][26] . Whether LE affected the neuronal uptake and nonneuronal uptake of NA is unknown, and the activation of α 2 -adrenoceptors and β 2 -adrenoceptors by NA was not ruled out in the study by Lee et al [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, a single oral dose of 1 mg DOXA resulted in peak plasma concentrations of 7.6 ng/ml at 3.6 hours, while hypertensive patients achieved 76 ng/ml within 2-3 hours with an 8 mg dose [ 34 ]. A pharmacokinetic study in non-fasted rodents has reported that after a single oral administration of 8 mg/kg DOXA, the plasma concentration was at 200 ng/ml at 2 h [ 36 ]. Therefore, we estimate that when 5 mg/kg DOXA used in our in vivo experiments was orally administered to mice as a single dose, peak plasma concentrations could be achieved at approximately 125 to 187.5 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Forty rats were randomly divided into five experimental groups (n = 8 each) as follows: Group 1 (control), Group 2 (sham operated), Group 3 (IR injury only), Group 4 (rats received doxazosin, 8 mg/kg), Group 5 (rats received dapagliflozin 10 mg/kg) . Drugs were given by oral gavage for 3 successive days prior to IR injury and 2 hours before euthanasia.…”
Section: Methodsmentioning
confidence: 99%